IL-33-Induced Cytokine Secretion and Survival of Mouse Eosinophils Is Promoted by Autocrine GM-CSF - Willebrand, Ralf; Vöhringer, David (PLoS ONE, 2016)
Eosinophils are major effector cells during allergic responses and helminth infections. Recent studies further highlight eosinophils as important players in many other biological processes. Therefore it is important to understand how these cells can be modulated in terms of survival and effector function. In the present study we investigated how eosinophils respond to the alarmin IL-33. We show that IL-33 promotes eosinophil survival in a ST2- and MyD88-dependent manner. IL-33-mediated protection from apoptosis was dependent on autocrine GM-CSF release. In addition, GM-CSF increased the IL-33-induced secretion of IL-4 and IL-13 from eosinophils. Unexpectedly, this effect was further enhanced by cross-linking of Siglec-F, a proposed inhibitory and apopotosis-inducing receptor on eosinophils. Co-culture experiments with eosinophils and macrophages revealed that the IL-33-induced release of IL-4 and IL-13 from eosinophils was required for differentiation of alternatively activated macrophages (AAMs). The differentiation of AAMs could be further increased in the presence of GM-CSF. These results indicate that cross-talk between Siglec-F and the receptors for IL-33, LPS and GM-CSF plays an important role for efficient secretion of IL-4 and IL-13. Deciphering the molecular details of this cross-talk could lead to the development of new therapeutic option to treat eosinophil-associated diseases.
EVALuna2:25883